Analysis of Overbooking Management Strategies at Garuda Indonesia Airline at Zainuddin Abdul Madjid Lombok International Airport - Furkan Furkan; Amelia Puspa Tamara (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the overbooking management strategy implemented by Garuda Indonesia Airlines at Zainuddin Abdul Madjid International Airport, Lombok. This study contributes to the field of management science by providing insights into operational decision-making, service recovery strategies, and customer relationship management in the aviation industry. The research method used is a qualitative analytical approach, with data obtained from primary data collected through observation and interviews and secondary data collected through documentation and literature studies. Data analysis was conducted using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. To test the validity of the data, triangulation techniques and a double-check process were used with respondents to ensure the suitability, accuracy, and consistency of the data obtained during the study. The results of the study indicate that overbooking generally occurs during peak travel periods, especially when major events are held in Lombok. The handling strategies implemented include reminders and confirmation of passenger departures, a personal approach in conveying information, strategies for identifying passengers affected by overbooking, rebooking flights, providing compensation and supporting facilities, upgrading service classes if available, providing waiting rooms during waiting times, as well as Ticket Sales Control and monitoring of passenger data. These findings emphasize the importance of strengthening operational controls, reservation system accuracy, and service coordination to minimize the impact of overbooking in order to maintain operational effectiveness and passenger satisfaction.